Pigâs farmerâs profile in Banyumas Regency - Hartoko, Hartoko (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
This research was purposed to study pigâs farmerâs profile in Banyumas Regency. The research was carried out since December 1999 to May 2000. It was located at Banyumas Regency.Â The method applied was survey with intensive observation, involved 51 respondents (54.26Â percent of total pig farmers in Banyumas Regency), consist of 7.80 percent women and 92.20 percent men. The result showed that pigâs farmer were in productive ageÂ (44 years) with low formal education level (Sekolah Dasar). Most of all are moeslems (90,16 percent) and had small family size (4-5 members). They have other income source and they rear pigs to generate income or to use soybean cakeâs waste (ampas tahu). Experience in the farming was quite long (more than 10 years) and skill come from imitating their neighbours, friends of other wise of autodidact. (Animal Production 2(1): 40-46 (2000)Â Key Words: profile, pigâs farmer, Banyumas, experience